1969
DOI: 10.1007/bf01406715
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the nuclear magnetic moment of110Ag(T 1/2=24.4 s)

Abstract: Nuclear magnetic resonance of ll~ has been observed in silver halides using the polarized neutron capture, fl decay anisotropy method. The magnetic moment was determined as ~I (la~ 2.7084 (5) nm (uncorrected).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1971
1971
1987
1987

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It should be noticed, however, that for the ground states of to6, tos, 110Ag ' where the spin I= 1 is due to the same nucleon configuration as in the metastable states, the agreement between the calculated moment (#f,cal~=3.15#,) and the measured moments (#~= 2.8 p, [12][13][14]) is less satisfactory. As pointed out by Noya, Arima, and Horie [15] configuration interaction may not be taken completely into account by using the empirical g-values; recently Callaghan [16] showed that there is an additional term arising from the coupling of the rotational motion of the core to the individual particle motion, which may differ in adjacent nuclei.…”
Section: I{ Jv(jv+ L)--j(j+ L)}mentioning
confidence: 73%
“…It should be noticed, however, that for the ground states of to6, tos, 110Ag ' where the spin I= 1 is due to the same nucleon configuration as in the metastable states, the agreement between the calculated moment (#f,cal~=3.15#,) and the measured moments (#~= 2.8 p, [12][13][14]) is less satisfactory. As pointed out by Noya, Arima, and Horie [15] configuration interaction may not be taken completely into account by using the empirical g-values; recently Callaghan [16] showed that there is an additional term arising from the coupling of the rotational motion of the core to the individual particle motion, which may differ in adjacent nuclei.…”
Section: I{ Jv(jv+ L)--j(j+ L)}mentioning
confidence: 73%
“…1. The evaluation of the nuclear magnetic moment of 11~ s) has already been reported in a previous communication [5]. Here, we are interested in another feature of these NMR signals, that is the asymmetry does not vanish in the center of the resonance.…”
Section: Dependence Of Fl Decay Asymmetry and Relaxation Time On The mentioning
confidence: 96%
“…The asymmetric/~ radiation was used in the cases of aLi [1], 2~ [2,3], 116In [4], 11~ [5], 28A1 [6], and 3~C1 [6] as a tool to detect nuclear magnetic resonance (NMR) signals from which nuclear moments were determined. Some of these isotopes have been investigated repeatedly [7 -9] in order to determine NMR line shapes as a function of radio frequency (rf) power, temperature and crystal orientation.…”
Section: Introductionmentioning
confidence: 99%